Transient heat transfer analysis in an internal combustion engine piston - Prasad R.; Samria N.K. (My University, 2025)
Numerical calculations based on finite difference approximations are carried out to assess the transient thermal response of an aluminium alloy piston of a semi-adiabatic diesel engine having a 1-cm-thick cast iron cylinder wall. The engine cylinder wall is coated externally by a 2-mm thin layer of oxide based ceramic insulating material. The non-ideal thermal contacts between the piston circumference and the cylinder wall are also considered. A detailed analysis is given for estimating the boundary conditions of the cylinder-piston assembly of an internal combustion engine. The isothermic distribution in the piston body and heat flow rates to cooling water and air below the piston at four different engine loads are depicted for cases both with and without insulation coating. The results indicate a 6% reduction in heat loss through the piston with the use of an insulation coating on the cylinder wall. © 1990.